Capital tax competition with three tax instruments - Wolfgang Eggert (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
The paper studies the role of capital mobility for efficiency of decentralized fiscal policies in a tax competition model where only a distorting wage, the residencebased and the source-based capital tax are available. We extend Bucovetsky and Wilson (1991) in deriving second-best taxation rules for small and large countries for each of the four possible combinations of tax instruments both in environments with an unconstrained and with a constrained set of tax instruments available to fiscal authorities. Whereas the model reproduces the result that countries underprovide local public goods in the absence of a residence-based capital tax, Nash equilibria are efficient in the two-tax cases if residence-based capital taxes but no source-based capital or else wage taxes are available. Moreover, aggregate production is situated on the world production frontier when the set of fiscal instruments is unrestricted.
Keywords: H73; H77; H21; F15; 330